2004
DOI: 10.1021/ja030653q
|View full text |Cite
|
Sign up to set email alerts
|

Electron Impact Ionization in Helium Nanodroplets:  Controlling Fragmentation by Active Cooling of Molecular Ions

Abstract: Reported here is a study of the effects of liquid helium cooling on the fragmentation of ions formed by electron impact mass ionization. The molecules of interest are picked up by the helium nanodroplets as they pass through a low pressure oven. Electron impact ionization of a helium atom in the droplet is followed by resonant charge transfer to neighboring helium atoms. When the charge is transferred to the target molecule, the difference in the ionization potentials between helium and the molecule results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 51 publications
11
82
0
Order By: Relevance
“…Miller and co-workers claimed that this point was reached when the helium droplets achieved an average size of approximately 40,000 helium atoms, as evidenced by the very small dopant signal in the mass spectrum [7]. This concurs roughly with our own experimental findings, although in our laboratory we have managed to obtain mass spectra with droplets with an estimated mean size of up to 60,000 atoms [18].…”
Section: Charge Transfer In Large Helium Dropletssupporting
confidence: 89%
“…Miller and co-workers claimed that this point was reached when the helium droplets achieved an average size of approximately 40,000 helium atoms, as evidenced by the very small dopant signal in the mass spectrum [7]. This concurs roughly with our own experimental findings, although in our laboratory we have managed to obtain mass spectra with droplets with an estimated mean size of up to 60,000 atoms [18].…”
Section: Charge Transfer In Large Helium Dropletssupporting
confidence: 89%
“…The work refined the ion hopping probability, and demonstrated that there is a long range steering, such that the He cation ion preferentially approaches the negative parts of the molecule, leading to regio-selective ionization. Fragmentation after ionization was studied for HCN [219] and the large organic molecule, triphenyl-methanol [220].…”
Section: Optically Selected Mass Spectroscopy In Helium Nanodropletsmentioning
confidence: 99%
“…A similar value was estimated by Lewis et al based on another ion, triphenyl methanol. 25 Note, however, that the cooling rates calculated from the rate constant suffer from a large uncertainty because of the difficulties in estimating rate constants in these systems. Thus the "direct" method is much more robust.…”
Section: A Excitation Transfer Processesmentioning
confidence: 99%